Diversification of processed products made from grass jelly leaves at the Teger Farmers Group, Semarang - Nofiyanto, Erwin; Haryati, Sri; Sudjatinah, Sudjatinah (Community Empowerment)
Food modification is still quite common in the community, especially the processing of candy, jelly drinks and dawet. The manufacture of candy, jelly drinks and dawet can be modified from the raw material of grass jelly leaves which have a lot of protein and vitamin content. The women of the Teger Farmer Group, Mangunsari Village, Gunungpati District, Semarang City mostly work as farmers and factory workers and do not quite know what food modification is, especially those made from grass jelly leaves. There are many grass jelly plants in the environment around the Teger Farmer Group that have not been utilized until now, so we aim to provide information to the Teger Farmer Group's mothers about preparations made from grass jelly leaves, which can be made into candy, dawet and jelly drinks that have a lot of content. nutrition. The service method was carried out with lectures, discussions and simulations of making processed products. The results of the service revealed that the Teger Farmers' Group, Mangunsari Village, Gunungpati District, Semarang City, mostly had eaten dawet and grass jelly drink, but had never eaten grass jelly candy. In addition, they also do not know how to make sweets, jelly drinks and dawet from grass jelly, and do not know what the ingredients are. Furthermore, at the end of this service activity, partners better understand how to make and nutritional content of all processed products from grass jelly.